Modelling Workability of Asphalt concrete Performance at different Temperatures using A Statistical Model - Arshad, Ahmad Kamil; Diah J, Md; Khalil, Salah (International Journal of Engineering and Technology, 2013)
In this study, a workability model is used to predict the values of Torque in relation to mix and compaction by Temperature, Gyration, Resilient Modulus, Stability and Flow. The data are obtained from workability-measuring devices developed by the authors. The value of R2 implies that about 95 % variation in the values of Torque can be explained by the variation in mixing and compaction according to Temperature, Gyration, and Resilient Modulus. The regression model as a whole shows that while the value of Torque is largely influenced by Compaction, Mixing Temperature and Gyration; Resilient Modulus, Stability and Flow are not significant determinants of workability. The paper recommends that the effect of workability on the performance of Asphalt concrete should be taken very seriously during the design.